PENERAPAN STANDAR RESEP DALAM PEMBUATAN SALAD DI COLD KITCHEN HOTEL PANGERAN PEKANBARU - Ega Maulidina. A Maulidina. A; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Hotel Pangeran Pekanbaru in making salads must have a good and correct recipe standard from the start of preparation, the process of making and serving. This is done so that the salad has a very good quality. This study aims to determine the application of standard recipes in making salads in the cold kitchen of Pangeran Pekanbaru Hotel. A recipe standard is an agreement on technical specifications that are used in instructions that explain how to make to a predetermined presentation. Standard recipes also have a goal to maintain consistency in terms of taste, texture, state of the mixture of ingredients and appearance. Cold Kitchen is a section in the kitchen that is assigned to make various cold foods. This study uses a qualitative method with a descriptive approach. The data collection technique in this study uses observation, documentation, interviews so that a very clear picture can be obtained. The informants in this study were Executive chef, Sous chef and 2 guests. Based on the research shows that the application of standard recipes in making salads in the cold kitchen of Pangeran Pekanbaru Hotel can be categorized as poor and has not applied good and correct recipe standards. Keywords : Application, Recipe Standard, Cold Kitchen,Hotel, Salad